2015
DOI: 10.1111/are.12962
|View full text |Cite
|
Sign up to set email alerts
|

The use of fenugreek seed meal in fish diets: growth performance, haematological and biochemical parameters, survival and stress resistance of common carp (Cyprinus carpioL.)

Abstract: The present study was conducted to investigate the effects of fenugreek seed meal (FKSM) on growth performance, blood haematological and biochemical factors, survival and stress resistance of the common carp (2.46 AE 0.06 g) fingerlings.Four practical diets containing 0 (control), 0.5%, 1% and 1.5% FKSM were used to feed fish. Fish were fed on the tested diets at a rate of 3% of body weight for 8 weeks. Results indicated that fish fed the control diet had a significantly lower weight gain, specific growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…Recently, there has been increasing interest in the potential use of FKSM in the diets of fish, and the results so far are promising. Roohi et al (2017) found that among the FKSM levels of 5, 10…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, there has been increasing interest in the potential use of FKSM in the diets of fish, and the results so far are promising. Roohi et al (2017) found that among the FKSM levels of 5, 10…”
Section: Discussionmentioning
confidence: 99%
“…Roohi et al. () found that among the FKSM levels of 5, 10 and 15 g/kg as supplements, the latter two significantly improved the growth and FCR in common carp. Similarly, Bahi et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth to mention that plants can also induced antioxidant enzymes such as catalase, superoxide dismutase, glutathione Stransferase, and peroxidases, which play an important role in detoxification and removal of toxicity-induced reactive oxygen species Abdel-Tawwab et al, 2018). In this regard, an interest in using fenugreek (Trigonella foenum graecum L.) [FN], in fish diets has gained attention in recent years (Mostafa et al, 2009;Mehboob et al, 2017;Roohi et al, 2017). The leaves of FN are used in diets as green leafy vegetables, which is rich in vitamins and minerals (Srinivasan, 2006;Roohi et al, 2017) and its seeds are used for medication in different countries for aphrodisiac effects, tonic and carminative (Xue et al, 2007).…”
mentioning
confidence: 99%